Comparison of the Effectiveness of Short-Term Intensive Dynamic Psychotherapy (ISTDP) and Schema Therapy for Mothers on Social Anxiety in Children Aged 5 to 6 - Beigi Harchegani, Niloufar; Ghazanfari, Ahmad (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Social anxiety disorder is among the most common disorders during childhood and adolescence. The present study aimed to compare the effectiveness of short-term intensive dynamic psychotherapy (ISTDP) and schema therapy for mothers on social anxiety in children aged 5 to 6 years in Shahin Shahr.Methods and Materials: This research was a quasi-experimental study with a pre-test, post-test, and follow-up design, including a control group. The research population consisted of all mothers of children aged 5 to 6 years with social anxiety in Shahin Shahr in 2023, from which 45 individuals were purposively selected based on scoring two standard deviations above the mean on the Spence Children's Anxiety Scale (Parent Version) and other entry criteria of the study, and were randomly assigned to two experimental groups and one control group (each containing 15 individuals). One experimental group received 10 weekly sessions of 90 minutes of schema therapy, while the second experimental group underwent 10 weekly sessions of 90 minutes of short-term intensive dynamic psychotherapy (ISTDP). The control group did not receive any intervention. The research tool was the Spence Children's Anxiety Scale (Parent Version, 1999), completed by the mothers at three stages: pre-test, post-test, and a 3-month follow-up. The obtained data were analyzed using repeated measures ANOVA, mixed-design ANOVA, and Bonferroni post-hoc tests with SPSS software version 24.Findings: The results showed that both treatments were effective in improving children's social anxiety (P